Assessment of the Symptoms of Premenstrual Syndrome in Physically Active and Sedentary Adult Women - Arruda, Luisa Muller; Martins, Luana Selaimen; Moreira, ThaÃs Rodrigues (Journal of Nutritional Therapeutics, 2017)
To assess the symptoms of premenstrual syndrome (PMS) and the nutritional status of physically active and sedentary adult women. This case-control study included 60 women, aged 18 to 35 years, recruited from two fitness centers or from an outpatient nutrition clinic. Four evaluations were conducted, on the follicular and luteal phase in two months. Questionnaires were applied to collect information about the socioeconomic condition and PMS symptoms. Weight and height were measured to calculate body mass index. Electrical bioimpedance was used to determine body composition, and food consumption was assessed using a food frequency questionnaire. The Student's t test and Chi-square test were applied to compare means and proportions between the groups. The occurrence of PMS was observed in 63.3% of women in the physically active group and 86.7% of participants in the sedentary group (p=0.074). Analysis of results relative to food consumption showed in the physically active group a low calorie consumption in 53.3% and 33.3% of the participants in the pre- and post-menstrual phases, respectively (p=0.039). In the sedentary group, a high calorie consumption was observed in 43.3% and 23.3% of the participants in the pre- and post-menstrual phases, respectively (p=0.007). The sedentary group presented carbohydrate consumption of 281.9 ± 61.1 grams and 252.1 ± 55.9 grams in the pre- and post-menstrual phases, respectively (p=0.001); increased consumption of lipids was also observed in these phases, 74.4 ± 23.4 grams 63.2 ± 19.4 grams, respectively (p=0.001). The results show that the sedentary group presents an increased frequency of PMS and increased consumption of calories, carbohydrates, lipids and sodium. In the physically active group there was association between reactance and fat percentage.